Medical students' conceptualisation of health advocacy in an interactive programme. Issue 6 (17th August 2020) - Midik, Ozlem; Coskun, Ozlem
ABSTRACT: This study aims to reveal to what degree the preclinical medical students' conceptualisation of health advocacy changes prior to and after the implementation of the "Roles of The Doctor" curriculum. The essay assignments obtained at the pre-and post-sessions of the health advocacy theme and the students' feedback about the programme were used. The analyses were performed following Miles and Huberman's guidelines on qualitative analysis. Before the elective course was implemented, very few students had conceptualizations about health advocacy. The conceptualizations that indirectly referred to health advocacy were responsibility, altruism, and justice, knowing and defending one's rights, looking after the patient, professional political understanding, responsibility and equality. The students defined the concept of health advocacy at three levels and under eight categories after health advocacy theme. They also defined the competencies of health advocate physicians. Offering the advocacy curriculum in the preclinical period enables the development of students' schemata related to the concept of health advocacy. This should be considered a step towards the development of professional identity. Students have dealt with health advocacy in terms of the protection of health professionals. This situation suggests that cognitive and emotional reaction arising from the increase in the cases of violence against professionals.